The Tradition Of Ngaji Jama' (A Study Of Living Qur'an In The Dompu Community, West Nusa Tenggara) - Nurul Aulia (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2024)
This Living Qur'an research discusses the tradition (Ngaji Jama') of reading the Qur'an using the rhythm of tartil and tilawah. Ngaji Jama' is a religious ritual performed by the people of Bima and Dompu, West Nusa Tenggara. It is held at night (Ba'da Isha). The series of events of the Ngaji Jama' tradition are: Wedding, circumcision and Tahlilan by chanting the Qur'an using rhythm together or taking turns. This study aims to find out the process of Ngaji Jama' in the tradition of religious rituals carried out at Ngaji Jama' Wedding, Khitanan and Tahlilan events. Furthermore, to find out what impact Ngaji Jama' has on the social life of the people of Dompu, West Nusa Tenggara. The recitation of the Qur'an undergoes transmission and transformation, namely, the Recitation of the Qur'an in the Companions Era, the Recitation of the Qur'an in the Middle Era and the Recitation of the Qur'an in the Contemporary Era. In this study the author used descriptive, qualitative methods, then strengthened by primary data sources, secondary data and analyzed the data by collecting data through observation, interviews and documentation. This research was conducted by interviewing several religious leaders as well as reciters and Qariahs among the Dompu community. Based on the results of the research, it can be concluded that the people of Dompu understand the Qur'an not only as a holy book, but also as the embodiment of an ideal society that is always close to the Qur'an. This is what distinguishes the Ngaji Jama' tradition from other regions when there is a formal or non-formal event. Keywords: Kata Tradition, Ngaji Jama???, Living Qur'an